과학관 전시물 연계 동화 활용 스토리텔링 수업이 초등학생의 과학학습정서에 변화를 가져온 요인 분석 - 최소영; So-young Choi; 신영준; Youngjoon Shin (Journal of Science Education, 2019)
본 연구는 과학관 전시물 연계 동화 활용 스토리텔링 수업이 초등학생의 과학 긍정경험에 어떤 영향을 주는지 알아보고자 한 것이다. 연구를 위해 동화를 과학관 전시물과 연관시켜 학교 밖에서도 개인이 과학을 탐구할 수 있도록 탐방활동지를 개발하였다. 초등교과서에 언급되어지는 동화 4종을 G 과학관 전시물과 연계시켜 활동지 4종류를 개발하였고, 개발된 활동지는 현직 초등교사 7명에게 검토를 의뢰하여 내용 검증을 거쳤다. 개발한 활동지를 통한 수업은 10명의 학생을 대상으로 매번 1시간 30분씩 연속 4회 진행하였다. 연구 참여 학생들을 대상으로 과학긍정경험 검사를 실시하여 본 활동이 과학긍정경험의 하위 영역 중 과학학습정서에 유의미한 변화를 일으켰음을 확인하였다. 과학학습정서에 영향을 미친 요인을 알아보기 위해 연구 참여 학생들과 참여 학생의 학부모를 대상으로 면담을 실시하였다. 본 연구의 결과를 종합해보면 동화를 전시물과 함께 활용하면 과학적 호기심을 유발시켜 과학적 사고를 하는데 도움을 주고, 과학적 흥미를 유발시켜 놀이장소로 인식하는 과학관전시물체험을 통해 학습 부담감을 감소시켜 과학에 대한 과학학습정서에 유의미한 변화가 있었음을 알 수 있었다. This study aims to find how storytelling classes using fairy tales related to science museum exhibits have an effect on positive experience about science. For this study, the theoretical background and preceding studies on the relevance of science education and literature were collected and based on the characteristics of assimilation and the educational value of assimilation, naturally connected to the exhibits in relation to their own life, so that individuals could explore science even out-of-school. Four types of activities were developed by linking four fairy tales mentioned in elementary school textbooks to the G science museum exhibits. Seven elementary school teachers verified the validity of the activity materials. Classes through the developed activity materials were conducted four times in a row, one and a half hours at every turn for 10 students. A positive experience about science test was conducted on the students in a study to confirm that this activity has caused significant changes in science academic emotion among sub-domains of positive experience about science. In order to find the factors that affected the science academic emotion, we interviewed the students in the study and their parents. The results of this study show that the use of fairy tales related to science museum exhibits has led to a significant change in science academic emotion by reducing the burden of learning through the exhibition experience at the science museum, which creates scientific curiosity and recognizes them as a playground.